NOX1 and NOX2: Two enzymes that promote endothelial-to-mesenchymal transition induced by melanoma conditioned media - Valentin Platel; Diane Lechevalier; Clara Bourreau; Sarah Renault; Ivana Šoborová; Caroline Jeannière; Ludovic Martin; Olivier Hérault; Isabelle Corre; Nicolas Clere (Elsevier, 2022)
Tumor microenvironment plays an important role in melanoma progression. Recent studies reported endothelial cells (EC) are involved in endothelial-to-mesenchymal transition (EndMT). During this phenotypic switch, EC progressively lose their endothelial markers and acquire mesenchymal properties. Depending on their concentration, reactive oxygen species (ROS) can control tumor growth. In EC, ROS are mainly produced by NAPDH oxidases (NOX) such as NOX1 and NOX2. The aim of the present study was to determine the role of these enzymes in EndMT induced by conditioned media (CM) from SK-MEL 28 melanoma cells. The capacity of CM to induce EndMT in HUVEC after 24 h, 48 h or 72 h has been evaluated by following endothelial HUVECs proliferation, migration and their capacity to form capillary on ECMgel®. Furthermore, EndMT was confirmed by western blot and flow cytometry. To determine the role of NOX in EndMT, specific NOX1 and/or NOX2 inhibitors has been tested. TGF-β2 + /- IL-1β was used as positive control. ROS production was determined through DCFDA assay. An altered endothelial phenotype was found in CM-treated HUVECs. This phenotypic modification was correlated with a decrease in both capillary formation on ECMgel® and cell proliferation and an increase in cell migration. Exposure to CM for 48 h significantly enhanced intracellular HUVECs ROS production and this increase was prevented by the dual pharmacological inhibition of NOX1 and NOX2. Furthermore, inhibition of NOX1/2 also leads to a partial reversion of CM-induced EndMT. These data confirmed the role of NOX1 and NOX2 in EndMT induced by melanoma cancer cell secretome.